O DIREITO À INCLUSÃO DIGITAL DAS PESSOAS COM DEFICIÊNCIA VISUAL NO BRASIL - JERUSA GABRIELA FERREIRA (2023)
This study, using the methodology of qualitative research, anchored in document analysis, focuses on the following research problem: The right to accessibility for people with disabilities guaranteed in the Brazilian Federal Constitution, in the Convention on the Rights of Persons with Disabilities and in the Law Is the Brazilian Inclusion Guide enough to ensure the digital inclusion of visually impaired people in Brazil? As an objective, the research sought to understand the legal panorama of the inclusion of people with visual impairments through accessibility, demonstrating the existing barriers within the use of the web. The analysis of the Theory of Recognition was carried out, in the model proposed by Axel Honneth and of the parallel critical theories, using the ideals of Charles Taylor and Nancy Fraser. Finally, this study analyzed the concept of accessibility defined by Brazilian and international standards, its implications and how digital accessibility is fundamental in the inclusion process. It was also found that assistive technologies related to the use of the web are robust and receive significant investment, so that Brazil has a range of assistive technologies for people with visual impairments and that they help a lot in this process, especially in the educational aspect. Thus, as a result, it remained evident that, although the person with disability has their right to digital inclusion assured in the online environment, the role of the Public Power is insufficient to provide the tools for digital inclusion to be implemented in our country.